Neuroprotection in stroke: the importance of collaboration and reproducibility. - Neuhaus, A; Couch, Y; Hadley, G; Buchan, A (Oxford University Press, 2017)
Acute ischaemic stroke accounts for 6.5 million deaths per year, and by 2030 will result in the annual loss of over 200 million disability-adjusted life years globally. There have been considerable recent advances in the gold standard of acute ischaemic stroke treatment, some aspects of which-aspirin to prevent recurrence, and treating patients in specialized stroke wards-are widely applicable. Recanalization of the occluded artery through thrombolysis and/or endovascular thrombectomy is restricted to only a small proportion of patients, due to contra-indications and the costs associated with establishing the infrastructure to deliver these treatments. The use of neuroprotective agents in stroke has been a notable failure of translation from medical research into clinical practice. Yet, with the advent of endovascular thrombectomy and the ability to investigate patients in much greater detail through advanced imaging modalities, neuroprotective agents can and should be re-examined as adjunct therapies to recanalization. In parallel, this requires appropriate planning on behalf of the preclinical stroke research community: there is a need to reinvestigate these therapies in a more collaborative manner, to enhance reproducibility through reduced attrition, improved reporting, and adopting an approach to target validation that more closely mimics clinical trials. This review will describe some of the novel strategies being used in stroke research, and focus on a few key examples of neuroprotective agents that are showing newfound promise in preclinical models of stroke therapy. Our primary aim is to give an overview of some of the challenges faced by preclinical stroke research, and suggest potential ways to improve translational success.